Case studies of damage to 19-storey irregular steel moment-frame buildings under near-source ground motion. - Krishnan, Swaminathan
This paper describes the three-dimensional nonlinear analysis of six 19-storey steel moment-frame buildings, designed per the 1997 Uniform Building Code, under strong ground motion records from near-source earthquakes with magnitudes in the range of 6.7?7.3. Three of these buildings possess a reentrant corner irregularity, while the remaining three possess a torsional plan irregularity. The records create drift demands of the order of 0.05 and plastic rotation demands of the order of 4?5% of a radian in the buildings with reentrant corners. These values point to performance at or near ?Collapse Prevention?. Twisting in the torsionally sensitive buildings causes the plastic rotations on the moment frame on one face of the building (4?5% of a radian) to be as high as twice of that on the opposite face (2?3% of a radian). The asymmetric yield pattern implies a lower redundancy in the lateral force-resisting system as the failure of the heavily loaded frame could result in a total loss of resistance to torsion.
Keywords: Tall buildings; Moment-frames.; Near-source ground motion; Irregularity